N6-methyladenosine methylation in ophthalmic diseases: From mechanisms to potential applications - Bingyan Li; Zicong Wang; Haixiang Zhou; Jingling Zou; Shigeo Yoshida; Yedi Zhou (Heliyon, 2024)
N6-methyladenosine (m6A) modification, as the most common modification method in eukaryotes, is widely involved in numerous physiological and pathological processes, such as embryonic development, malignancy, immune regulation, and premature aging. Under pathological conditions of ocular diseases, changes in m6A modification and its metabolism can be detected in aqueous and vitreous humor. At the same time, an increasing number of studies showed that m6A modification is involved in the normal development of eye structures and the occurrence and progress of many ophthalmic diseases, especially ocular neovascular diseases, such as diabetic retinopathy, age-related macular degeneration, and melanoma. In this review, we summarized the latest progress regarding m6A modification in ophthalmic diseases, changes in m6A modification-related enzymes in various pathological states and their upstream and downstream regulatory networks, provided new prospects for m6A modification in ophthalmic diseases and new ideas for clinical diagnosis and treatment.